The Day of the Week Effect in the Crypto Currency Market - Guglielmo Maria Caporale; Alex Plastun (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper examines the day of the week effect in the crypto currency market using a variety of statistical techniques (average analysis, Student's t-test, ANOVA, the Kruskal-Wallis test, and regression analysis with dummy variables) as well as a trading simulation approach. Most crypto currencies (LiteCoin, Ripple, Dash) are found not to exhibit this anomaly. The only exception is BitCoin, for which returns on Mondays are significantly higher than those on the other days of the week. In this case the trading simulation analysis shows that there exist exploitable profit opportunities that can be interpreted as evidence against efficiency of the crypto currency market.
Keywords: G12; C63; 330; efficient market hypothesis; day of the week effect; crypto currency; BitCoin; anomaly; trading strategy